Duration of Disease and Long‐Term Outcomes in Patients With Difficult‐To‐Treat Recurrent Pericarditis: A Chronic Condition Treated With Nonsteroidal Anti‐Inflammatory Drugs, Colchicine, Corticosteroids, and Anti–Interleukin‐1 Agents - Elisa Ceriani; Francesco Agozzino; Silvia Berra; Antonio Gidaro; Paolo Bindi; Alberto Pavarani; Silvia Macchi; Letizia Vena; Francesco Moda; Ludovico Luca Sicignano; Celeste Ambra Murace; Laura Gerardino; et al. (ACR Open Rheumatology)
Objective We aimed to investigate the remission rate and disease duration in idiopathic or post–cardiac injury pericarditis and risk factors for disease duration and anti–interleukin‐1 (IL‐1) agent discontinuation. Methods This was a multicenter, longitudinal, observational study including 370 patients (51.4% female). The remission rate was the proportion of patients who stopped all pericarditis‐related therapies for at least 6 months without recurrences. Results The median follow‐up was 4.9 (interquartile range [IQR] 2.8–8.4) years, and the median age at the end of follow‐up was 49 (IQR 37–60) years. A median of 1.1 (IQR 0.6–1.9) recurrences/year and 0.4 (IQR 0.1–0.9) hospitalizations/year were recorded. The remission rate at follow‐up was 34.0%, 7% per year. Disease duration was shorter for patients in remission (3.1 years, IQR 1.6–6.2 years) than for those still receiving treatment (4 years, IQR 2.2–7.8; P = 0.02). Use of “guidelines‐based therapy” (hazard ratio [HR] 1.85, 95% confidence interval [CI] 1.25–2.73; P = 0.02) and colchicine use at first attack (HR 1.51, 95% CI 1.02–2.23; P = 0.038) were protective factors, whereas steroid use was associated with longer disease duration (HR 0.53, 95% CI 0.35–0.81; P = 0.003). Corticosteroids were used in 77.3% of patients, with a median duration of therapy of 1.1 (IQR 0.4–2.6) years. Anakinra was used in 25.9% with a median duration of therapy of 2.4 (IQR 0.9–5.0) years; only 19.8% were able to stop anakinra at the end of observation period. Conclusion This study reports the largest and longest follow‐up in patients with recurrent pericarditis. Guideline adherence from the first attack is associated with a shorter course. The disease was long and impacting in terms of recurrences and hospitalizations, often requiring a long‐term treatment, in particular with anti–IL‐1 agents.